2008
DOI: 10.1007/s11187-008-9122-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of ethnic self-employment in time and space: evidence from British Census microdata

Abstract: Self-employment, Ethnicity, Immigrants, J23, J7, L26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
(36 reference statements)
1
43
1
1
Order By: Relevance
“…the broader national and regional policies related to university-industry interactions and the perception of different types of universities in the eyes of policy makers and the potential collaboration partners) as potential determinants of academics' behavioural responses. This decomposition method, which originated from labour economics, has more recently been implemented in entrepreneurship studies that examine the impact of factors such as gender, race, ownership, ethnicity and immigration status on various forms of entrepreneurial activities (Block et al 2015;Clark and Drinkwater 2010;Wagner 2008;He 2008;Lofstrom and Bates 2009 amongst others).…”
Section: Methodsmentioning
confidence: 99%
“…the broader national and regional policies related to university-industry interactions and the perception of different types of universities in the eyes of policy makers and the potential collaboration partners) as potential determinants of academics' behavioural responses. This decomposition method, which originated from labour economics, has more recently been implemented in entrepreneurship studies that examine the impact of factors such as gender, race, ownership, ethnicity and immigration status on various forms of entrepreneurial activities (Block et al 2015;Clark and Drinkwater 2010;Wagner 2008;He 2008;Lofstrom and Bates 2009 amongst others).…”
Section: Methodsmentioning
confidence: 99%
“…Basu 1998;Fairlie 2004;Clark and Drinkwater 2008). These differences have been attributed to a mixture of ''push'' (threat) and ''pull'' (opportunity) factors promoting entrepreneurial activities (Constant and Zimmermann 2006;Clark and Drinkwater 2008;Basu 1998;Uhlaner and Thurik 2007). The push factors include the economic or institutional environment (e.g.…”
Section: The Overseas Chinese In Malaysiamentioning
confidence: 99%
“…Some of these original migrants still worked in those occupations at the time of the 2001 Census. In addition, many of their o spring who grew up in Great Britain were already in the labor market at that date (Clark and Drinkwater 2007). Certainly, the labor supply of migrants' descendants is not necessarily tied to the occupational niches in which their forebears found work particularly if these niches were not very attractive or advantageous (Waldinger and Feliciano 2004) or were in economic sectors that have declined over the years (Allen and Massey 1988;Cross 1992;Crouch 1999).…”
Section: Traditional Notions: Ethnic Segregation and Gender Segregationmentioning
confidence: 99%
“…Certainly, the labor supply of migrants' descendants is not necessarily tied to the occupational niches in which their forebears found work particularly if these niches were not very attractive or advantageous (Waldinger and Feliciano 2004) or were in economic sectors that have declined over the years (Allen and Massey 1988;Cross 1992;Crouch 1999). Nevertheless, many observers have concluded that there are substantial di erences in economic performance between people with immigrant origins and the rest of the labor force (Berthoud 2000;Clark and Drinkwater 2007;Fernández 2010;Heath and Yu 2005). For example, ethnic minority entrepreneurs concentrate in the retail, catering, and transport sectors (Parker 2004) but are underrepresented in professional and intermediate non-manual occupations (Carmichael and Woods 2000).…”
Section: Traditional Notions: Ethnic Segregation and Gender Segregationmentioning
confidence: 99%
See 1 more Smart Citation